A survey about clinical rotation in department of dermatology and demands for case database of dermatology on eight-year medical students at Peking Union Medical College - WU Chao, WANG Hai-meng, LI Li, LI Hong-chun, JIN Hong-zhong (Jichu yixue yu linchuang, 2020)
Objective To investigate the teaching demands and practical effects of rotation in department of dermatology as well as demands for case database on eight-year medical students at Peking Union Medical College (PUMC). Methods From January 2017 to January 2019,the questionnaire survey was issued to the eight-year medical students of the 2011 to 2014 grade,which investigated the demands of the rotation,the difficulty in learning, the degree of mastery and demands for case database. Results A total of 101 valid questionnaires were received,which showed that the eight-year medical students at PUMC had a strong interest in the diagnosis and treatment of common and uncommon skin diseases as well as medical cosmetology. Autoimmune bullous disease was the most difficult chapter to learn. The eight-year medical students at PUMC had a strong demand for dermatology case database. They hoped to share it electronically. The most interesting content in the database was allergic skin disease. Conclusions The difficulties and weakness in dermatology teaching for eight-year medical students at PUMC and students' demands for dermatology case database are initially clarified,which may support is the improvement of learning outcome in dermatology.